QUICK RASIO, DEBT EQUITY RASIO, DAN INVENTORY TURNOVER DALAM MEMPENGARUHI RETURN ON ASSET SERTA DAMPAKNYA BAGI KEBIJAKAN DEVIDEN PADA PERUSAHAAN SUB SEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Prasetyo, Muhammad Yolan Huri; Hamdun, Edy Kusnadi; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2025)
The ability to manage dividend distribution is a complicated problem due to differences in interests between company management and shareholders. This study aimed to analyze the effect of Quick Ratio, Debt Equity Ratio, and Inventory Turnover in Influencing Return On Asset and its Impact on Dividend Policy. The population in this study consisted of mining sector companies listed on the IDX. This study's data analysis and hypothesis testing used the Structural Equation model -Partial Lest Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that the Quick Ratio has a negative and insignificant effect on Return On Asset, Debt Equity Ratio, and Inventory Turnover have a positive but insignificant effect on Return On Asset, Quick Ratio, and Inventory Turnover have a positive but insignificant effect on dividend policy, Debt Equity Ratio has a significant negative effect on dividend policy, Quick Ratio has a positive but insignificant effect on dividend policy through Return On Asset, Quick Ratio, and Inventory Turnover have a positive but insignificant effect on dividend policy through Return On Asset, Debt Equity Ratio has a negative and insignificant effect on dividend policy through Return On Asset